Human striatal progenitor cells that contain inducible safeguards and overexpress BDNF rescue Huntington’s disease phenotypes - Danielle A. Simmons; Sridhar Selvaraj; Tingshuo Chen; Gloria Cao; Talita Souto Camelo; Tyne L.M. McHugh; Selena Gonzalez; Renata M. Martin; Juste Simanauskaite; Nobuko Uchida; Matthew H. Porteus; Frank M. Longo (Molecular Therapy: Methods & Clinical Development)
Huntington’s disease (HD) is an autosomal-dominant neurodegenerative disorder characterized by striatal atrophy. Reduced trophic support due to decreased striatal levels of neurotrophins (NTs), mainly brain-derived neurotrophic factor (BDNF), contributes importantly to HD pathogenesis; restoring NTs has significant therapeutic potential. Human pluripotent stem cells (hPSCs) offer a scalable platform for NT delivery but have potential safety risks including teratoma formation. We engineered hPSCs to constitutively produce BDNF and contain inducible safeguards to eliminate these cells if safety concerns arise. This study examined the efficacy of intrastriatally transplanted striatal progenitor cells (STRpcs) derived from these hPSCs against HD phenotypes in R6/2 mice. Engrafted STRpcs overexpressing BDNF alleviated motor and cognitive deficits and reduced mutant huntingtin aggregates. Activating the inducible safety switch with rapamycin safely eliminated the engrafted cells. These results demonstrate that BDNF delivery via a novel hPSC-based platform incorporating safety switches could be a safe and effective HD therapeutic.